THE FORMATION OF MIGRANT COMMUNITIES IN NIGERIA: A STUDY OF GOBIRAWA SETTLEMENTS NIGER STATE, NIGERIA - Muhammad Mukhtar Gatawa (European Scientific Journal, ESJ, 2014)
This paper seeks to highlight the establishment and growth of Gobirawa migrant community in Niger State, Nigeria. Beginning with a pioneer group of a few men in 1973, the migrants are now found in many rural areas in the state; some in wholly Gobirawa settlements, others living in Gwari-based communities. It is also the aim of the paper to discuss the occupational activities – both farming and non-farming – of the migrants. While it is re-affirms that farming remains their major occupation, some migrants do engage themselves in non-farming activities such as hunting and trading, most especially after farm harvest season. The paper concludes that migration of labour and humans as well as inter-group relations and cultural integration have been part of the history of Nigerian societies.